2002
DOI: 10.4161/cc.1.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Promoter Elements Responsible for Transcriptional Inhibition of Polo-like Kinase 1 and Topoisomerase IIα Genes by p21WAF1/CIP1/ SDI1

Abstract: © 2 0 0 2 L a n d e s B i o s c i e n c e . N o t f o r d i s t r i b u t i o n .[Cell Cycle 1, 59-66, January 2002]; published online as a Cell Cycle "Papers In Press" at www. ABSTRACT Induction of p21 WAF1/CIP1/SDI1 , a physiological mediator of cell cycle arrest, inhibits multiple genes involved in cell division. We have investigated the determinants of p21-mediated inhibition of two of these genes, polo-like kinase 1 (PLK1) and topoisomerase IIα (TOPO IIα). p21 expression from an inducible promoter in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
75
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 32 publications
3
75
0
2
Order By: Relevance
“…Here, we found similarly that NO ⅐ repression of PLK1 transcription appeared completely dependent on p38 MAPK activation in PMA-differentiated U937 cells. These results and previous reports demonstrating that p21/Waf1 inhibits the expression of many late phase cell cycle genes including PLK1 (9,15,34) suggested that NO ⅐ -p38 MAPK signaling might exert its repressive effect on PLK1 transcription through up-regulation of p21/Waf1. Although alternative mechanisms, such as direct NO ⅐ effects on transcription factors that regulate PLK1 remain possible, the current experiments strongly implicate the importance of p21/Waf1 induction by NO ⅐ .…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Here, we found similarly that NO ⅐ repression of PLK1 transcription appeared completely dependent on p38 MAPK activation in PMA-differentiated U937 cells. These results and previous reports demonstrating that p21/Waf1 inhibits the expression of many late phase cell cycle genes including PLK1 (9,15,34) suggested that NO ⅐ -p38 MAPK signaling might exert its repressive effect on PLK1 transcription through up-regulation of p21/Waf1. Although alternative mechanisms, such as direct NO ⅐ effects on transcription factors that regulate PLK1 remain possible, the current experiments strongly implicate the importance of p21/Waf1 induction by NO ⅐ .…”
Section: Discussionsupporting
confidence: 73%
“…p21/Waf1 is a multipotent CDK inhibitor. By binding to CDK complexes, it inhibits CDK activities, resulting in retinoblastoma-associated protein dephosphorylation and subsequent sequestration of E2F family proteins (9,34). This is widely believed to be the mechanism by which p21/Waf1 down-regulates a large group of E2F-dependent genes involved in DNA replication and cell cycle progression (9,21,34).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations